2016
DOI: 10.1002/14651858.cd001909.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine add-on for drug-resistant partial epilepsy

Abstract: The basis for the assumed risk (e.g. the median control group risk across studies) is provided in footnotes 4 . The corresponding risk (and its 95% confidence interval) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI). CI: Confidence interval; RR: Risk Ratio. GRADE Working Group grades of evidence High quality: Further research is very unlikely to change our confidence in the estimate of effect. Moderate quality: Further research is likely to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…RE is a chronic and debilitating disease of the nervous system with epileptic seizure caused by accidental discharge of cerebral neurons, which may lead to stigma in patients ( 19-21 ). Therefore, appropriate inhibition of neuronal excitability is the key in selection of AEDs in RE children ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…RE is a chronic and debilitating disease of the nervous system with epileptic seizure caused by accidental discharge of cerebral neurons, which may lead to stigma in patients ( 19-21 ). Therefore, appropriate inhibition of neuronal excitability is the key in selection of AEDs in RE children ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine is an antiepileptic drug indicated as an adjunctive therapy in children above the ages of two specifically for primary generalized tonic-clonic seizures. It is also indicated for the treatment of bipolar disorder in patients (Ramaratnam, Panebianco, & Marson, 2016). Although the mechanism of action of this drug is unknown, in vitro pharmacological studies suggest that lamotrigine inhibits voltage-sensitive sodium channels, thereby stabilizing neuronal membranes and consequently modulating presynaptic transmitter release of excitatory amino acids (e.g., glutamate and aspartate).…”
Section: Discussionmentioning
confidence: 99%
“…For example, lamotrigine showed the same benefit on seizure in three reviews [25,80,82], or melatonin used to reduce sleep latency [44] showed no benefit both in adults and children.…”
Section: Discussionmentioning
confidence: 99%